The difference of students’ learning outcomes and science process skill which taught by guided inquiry and direct instruction with practicum integrated - Anna Juniar; Ratih Dwi Fardilah (Pascasarjana Universitas Negeri Medan, 2019)
This study aimed to determine differences of students’ learning outcomes and science process skill which taught by using the guided inquiry model and direct instruction where both models were integrated with practicum on the topic of colligative nature of electrolyte solutions. The population in this study were all students of class XII MIA Binjai SMA 5 consisting of 6 classes. The sample was determined by purposive sampling technique, which taking 2 classes: XII MIA-1 (as the experimental class-I) applied Guided Inquiry learning model and XII MIA-2 (as the experimental class-II) applied Direct Instruction where both were practicum integrated. This study was conducted using the Quasi Experimental design with non-equivalent group pretest-posttest design. Data collection was done for pre-test and post-test by using twenty items of multiple choices instruments which were valid and reliable for learning outcomes, meanwhile six items valid essay test for science process skill. The results showed that there were differences in the average value of learning outcomes and science process skill with the values of each t-statistics > t-table namely 7.082 > 2.0345 and 8.76 > 2.0345, while the difference in the average value of activities and attitudes of student learning during the learning process in the experimental classes I and II were 90.21 (very good) and 79.87 (good) and 88.54 (very good) and 77.43 (good). Based on the results of the questionnaire analysis, students agreed that Guided Inquiry model able to facilitate them in understanding the topic of colligative nature of electrolyte solutions because they could design their own experiments in practical activities.Keywords:Direct instruction; guided inquiry; student’s learning outcome; science process skills